Pengaruh Terapi Latihan Fase 1 Pada Kasus Median Meniscus Tear Knee Sinistra Di Klinik Esa Unggul : Studi kasus - Wahyu Rizki Fajar Rabbani; Totok Budi Santoso; Faisal Isra Maulana (LPPM STIKES Siti Hajar dan Insight Power, 2022)
Introduction: Meniscus tear is a condition where there is a tear or rupture of the cartilage that functions as a cushion or pressure reducer in the knee joint, meniscus injury has two types of causes, namely traumatic and degenerative. Signs and symptoms that often occur in meniscus tears are pain, subacute swelling, and mechanical symptoms such as friction, instability, limited range of motion, locking. The injury occurred due to a lot of activity. This study aims to determine the benefits of phase 1 exercise therapy in reducing pain, increasing the range of joint motion, increasing physical activity and functional ability in the case of the left median meniscus tear knee. After therapy for 3 meetings, the results were in the form of a decrease in motion pain which originally had motion pain having a value of 4 to a value of 2 and there was an increase in Manual Muscle Testing (MMT) in the extension movement of the left knee from the initial meeting of value 4 to a value of 5 and a change in Anthropometric examination on muscle atrophy increased in the tibial tuberosity which originally had a value of 33.5 cm, 36.8 cm, 39.8 cm to 33.5 cm, 37.5 cm, 40 cm the difference in anthropometry had 4 cm in the quadriceps . Increased physical activity and functional ability, with KOOS (Knee injury and Osteoarthritis Outcome Score), from a scoreof 79% to 94%. Therapy using Isometric Exercise and Exercise Therapy can accelerate pain reduction, increase muscle strength, and increase functional ability in Meniscus Tear conditions.Keywords: Meniscus Tear, Isometric Exercise and Exercise Therapy.